When We Began: The Origins ofJSP - Montagnes, Ian (Journal of Scholarly Publishing, 2019)
JSP was founded fifty years ago from the vision of Marsh Jeanneret and the pragmatism of Eleanor Harman, director and assistant director, respectively, of the University of Toronto Press. It was conceived in a golden age of scholarly publishing as a journal primarily of practical advice, for authors as well as publishers, presented in an elegant design. Rigorous research into its subject had not yet begun.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNTEuMS4wMQ